IMPLEMENTATION OF RELIGIOUS-BASED CHARACTER EDUCATION IN SOCIAL STUDIES SUBJECTS AT MTS NEGERI 1 TERNATE: IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS RELIGIUS MATA PELAJARAN IPS DI MTS NEGERI 1 TERNATE - Yusrin.N. Syamsudin; Rustam Hasim; Irwan Abbas (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the implementation of religious-based character education in Social Sciences (IPS) subjects at MTs Negeri 1 Ternate. Religious-based character education is considered important as a foundation for forming a generation that is not only academically intelligent, but also has good morals and ethics. This study uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation of IPS teachers, students, and principals at MTs Negeri 1 Ternate. The results of the study indicate that the implementation of religious-based character education in IPS subjects at MTs Negeri 1 Ternate has been going well, although there are several challenges, such as limited time and resources. Some character values ​​applied in IPS learning include discipline, honesty, responsibility, and mutual respect, which are taught through materials that integrate religious aspects in a social context. IPS teachers act as facilitators in instilling religious values ​​in students with various methods, such as lectures, group discussions, and field activities. Overall, this study concludes that the implementation of religious-based character education in social studies learning can support the formation of better student character, with an emphasis on religious values ​​that can enrich their learning experience. Therefore, further efforts are needed to strengthen the integration of character education in the curriculum and daily activities at school.